Lablab purpureus (L.) Sweet - diversity, potential use and determination of a core collection of this multi-purpose tropical legume - Pengelly, Bruce C.; Maass, Brigitte L. (Springer, 2001)
Two germplasm collections of Lablab purpureus L. Sweet totalling 249 accessions were grown in the field in Australia and Ethiopia and characterised using a common set of morphological and agronomic (M-A) attributes. Data from each site were analysed separately using multi-variate analysis and a classification constructed for each collection. There was considerable diversity within both collections, especially that maintained in Ethiopia. Time to flowering, seed weight, and plant height were the most important attributes in determining group allocation in both classifications. Both collections had a high proportion of L. purpureus subspurpureus, especially accessions similar to the Australian cultivars Highworth and Rongai. They also had good representation of the less common L. purpureus subsuncinatus Verdc. less common landraces and wild collections from either Africa or India. When combined, the two classifications provided an overview of diversity and highlighted the similarities and dissimilarities between the two collections. The vast range in plant types supported the view that lablab has the capacity to be a multi purpose legume for both commercial and smallholder agriculture. Some important and less common germplasm identified were Ethiopian domesticated subsuncinatus, Ethiopian subspurpureus landraces collected from regional markets, semi-domesticated and wild accessions from southern Africa, and wild accessions from India. Using this overview, a core collection of germplasm was selected, which provides researchers with a sound basis for future plant breeding and agronomic studies with this important tropical legume.